(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Intervertebral foramen is the doorway of nerve root, and it plays an important role of radiculopathy and surgical treatment of intervertebral foramen diseases. Objectives the aim of this study was to determine the effect of side-lying with same side rotation and opposite side bending trunk position on patient with posterior and posterior-lateral disc prolapse at T12 –L1 level. Subjects and methods This study was conducted on 20 male participants. The study was conducted in radiology center specialized in the spine under the supervision of teaching staff member of the radiology department. Participants were divided into two equal groups of 10. The first group (A) were patients with discogenic lesion and the second group (B) was for normal individuals. Both groups were scanned using 3D CT scan at two positions: supine position and oblique position. The measurements taken were the intervertebral foramen (IVF) length (L), width (W) and cross sectional area (A). Results Mixed design MANOVA revealed that there was no significant difference between supine and oblique groups in diseased group regarding L, W and A. The IVF dimensions (L and W) did not significantly change with changing the spine position, while (A) was significantly higher in group A compare with group B whether in supine position or oblique position. Conclusion Changing the spine position from supine to oblique rotation position had no significant effect on length and width dimensions of intervertebral foramen. Oblique position had a significant influence on increasing the IVF cross sectional area in patients with discogenic lesion.